A toolbox for generating single‐stranded DNA in optical tweezers experiments. Issue 9 (22nd June 2013) - Candelli, Andrea; Hoekstra, Tjalle P.; Farge, Geraldine; Gross, Peter; Peterman, Erwin J. G.; Wuite, Gijs J. L.
ABSTRACT Essential genomic transactions such as DNA‐damage repair and DNA replication take place on single‐stranded DNA (ssDNA) or require specific single‐stranded/double‐stranded DNA (ssDNA/dsDNA) junctions (SDSJ). A significant challenge in single‐molecule studies of DNA–protein interactions using optical trapping is the design and generation of appropriate DNA templates. In contrast to dsDNA, only a limited toolbox is available for the generation of ssDNA constructs for optical tweezers experiments. Here, we present several kinds of DNA templates suitable for single‐molecule experiments requiring segments of ssDNA of several kilobases in length. These different biotinylated dsDNA templates can be tethered between optically trapped microspheres and can, by the subsequent use of force‐induced DNA melting, be converted into partial or complete ssDNA molecules. We systematically investigated the time scale and efficiency of force‐induced melting at different ionic strengths for DNA molecules of different sequences and lengths. Furthermore, we quantified the impact of microspheres of different sizes on the lifetime of ssDNA tethers in optical tweezers experiments. Together, these experiments provide deeper insights into the variables that impact the production of ssDNA for single molecules studies and represent a starting point for further optimization of DNA templates that permit the investigation of protein binding and kinetics on ssDNA. © 2013 Wiley Periodicals, Inc. Biopolymers 99:611–620, 2013.